Low-defectiveness exfoliation of MoS2 nanoparticles and their embedment in hybrid light-emitting polymer nanofibers. Issue 46 (15th November 2018) - Portone, Alberto; Romano, Luigi; Fasano, Vito; Di Corato, Riccardo; Camposeo, Andrea; Fabbri, Filippo; Cardarelli, Francesco; Pisignano, Dario; Persano, Luana
Abstract : MoS2 nanoparticles are obtained through a highly gentle exfoliation method and are embedded in polymer nanofibers to make them light-emitting. Abstract : Molybdenum disulfide (MoS2 ) has been attracting extraordinary attention for its intriguing optical, electronic and mechanical properties. Here, we demonstrate hybrid, organic–inorganic light-emitting nanofibers based on MoS2 nanoparticle dopants obtained through a simple and inexpensive sonication process in N -methyl-2-pyrrolidone and successfully encapsulate the nanofibers in polymer filaments. The gentle exfoliation method used to produce the MoS2 nanoparticles results in low defectiveness and preserves the stoichiometry. The fabricated hybrid fibers are smooth, uniform and flawless and exhibit bright and continuous light emission. Moreover, the fibers show significant capability for waveguiding self-emitted light along their longitudinal axes. These findings suggest that emissive MoS2 fibers formed by gentle exfoliation are novel and highly promising optical materials for sensing surfaces and photonic circuits.